Automatic Leveling System of Catenary Operating Vehicle Based on PLC - Wu Yanping; Hui Lihua; Li Wu (机车电传动)
An automatic leveling system of catenary operating vehicle was discussed. Software programming was implemented withPLC and analog input module, which realized operation platform automatic leveling of catenary operating vehicle when outer rail wasover high. At the same time, with the automatic leveling system, the operation platform could be automatic reset.